Ovariectomy Impaired Hepatic Glucose and Lipid Homeostasis and Altered the Gut Microbiota in Mice With Different Diets - Lei, Zili; Wu, Huijuan; Yang, Yanhong; Hu, Qing; Lei, Yuting; Liu, Wanwan; Nie, Ya; Yang, Lanxiang; Zhang, Xueying; Yang, Changyuan; Lin, Ting; Tong, Fengxue; et al. (Frontiers in Endocrinology, 2021)
The lower incidence of metabolic diseases of women than men and the increasing morbidity of metabolic disorders of menopausal women indicated that hormones produced by ovaries may affect homeostasis of glucose and lipid metabolism, but the underlying mechanisms remain unclear. To explore the functions of ovaries on regulating glucose and lipid metabolism in females, 8 weeks old C57BL/6 mice were preformed ovariectomy and administrated with normal food diet (NFD) or high fat diet (HFD). Six weeks after ovariectomy, blood biochemical indexes were tested and the morphology and histology of livers were checked. The expression levels of genes related to glucose and lipid metabolism in liver were detected through transcriptome analysis, qPCR and western blot assays. 16S rDNA sequence was conducted to analyze the gut microbiota of mice with ovariectomy and different diets. The serum total cholesterol (TC) was significantly increased in ovariectomized (OVX) mice fed with NFD (OVXN), and serum low density lipoprotein-cholesterol (LDL-C) was significantly increased in both OVXN mice and OVX mice fed with HFD (OVXH). The excessive glycogen storage was found in livers of 37.5% mice from OVXN group, and lipid accumulation was detected in livers of the other 62.5% OVXN mice. The OVXN group was further divided to OVXN-Gly and OVXN-TG subgroups depending on histological results of the liver. Lipid drops in livers of OVXH mice were more and larger than other groups. The expression level of genes related with lipogenesis was significantly increased and the expression level of genes related with β-oxidation was significantly downregulated in the liver of OVXN mice. Ovariectomy also caused the dysbiosis of intestinal flora of OVXN and OVXH mice. These results demonstrated that hormones generated by ovaries played important roles in regulating hepatic glucose and lipid metabolism and communicating with the gut microbiota in females.